Whole blood long-chain n-3 fatty acids as a measure of fish oil compliance in children with acute lymphoblastic leukemia: a pilot study. (February 2022) - Laumann, R.D; Iversen, T; Frandsen, T.L; Mølgaard, C; Stark, K.D; Schmiegelow, K; Lauritzen, L
Highlights: Fish oil supplementation is feasible in children with acute lymphoblastic leukemia. Reported intake of n-3 LCPUFA reflects the relative content in whole blood. Intake-biomarker correlations were disrupted when expressed in absolute concentrations and intake per kg bodyweight. Whole blood n-3 LCPUFA response did not appear to be affected by blood transfusions and differences in bodyweight. Abstract: Long-chain n-3 fatty acids (n-3 LCPUFA) may prevent chemotherapy-induced hyperlipidemia in children with acute lymphoblastic leukemia (ALL). However, compliance could be a problem and intake-biomarker correlations may be affected by bodyweight and blood transfusions. We assessed whole blood n-3 LCPUFA three times during the first 83 days of treatment in six 1-17-year-old children with ALL, who received 2.4-4.9 g/d n-3 LCPUFA depending on bodyweight. Mean compliance was 73%, which resulted in a 2.5-fold increase in blood n-3 LCPUFA irrespective of blood transfusions. The correlation between relative blood content of n-3 LCPUFA and intake in g/d across the study period was strong (r=0.76, p=0.001). When n-3 LCPUFA was expressed in absolute concentrations and intake per kg bodyweight the correlation decreased (r=0.39, p=0.164) and was driven by baseline values. Thus, relative content of n-3 LCPUFA in blood reflects fish oil compliance in children with ALL despite blood transfusions and differences in bodyweight.